Modelagem do potencial geoturístico do Parque Estadual Serra do Rola Moça - MG - Dayane Leticia Rodrigues dos Reis (2018)
Conservation of the environment is a subject that has received prominence in both the international and national scientific literature, and there are several initiatives focused on the awareness of nature conservation. These initiatives have contributed considerably to the increase in visitation in natural areas and the emergence of new forms of tourism such as geotourism. This work aimed to investigate the geotourism potential of the Serra do Rola Moça State Park (PESRM). The methodology used to generate the map of this potential was the multicriteria analysis. Initially, the input variables were modeled: environmental vulnerability, capillarity and visibility. In order to produce the map of environmental vulnerability, the following variables were combined: geology, pedology, geomorphology (Roughness Concentration Index - ICR) and vegetation cover. The capillarity map was constructed from the calculation of the density of the roads considered, paved, unpaved roads and trails belonging to the PESRM management plan, using the Kernel statistical method. The visibility map was elaborated from the crossing of the relief data and lookouts. The map of potential geotourism generated allowed the selection of nine geodiversity sites located in areas of high tourism potential that were inventoried and evaluated qualitatively and quantitatively and regarding the risk of degradation with emphasis on tourist use. Actions that may contribute to the success of geotourism activities in the area were suggested and a proposed geotourism script. In conclusion, it was evidenced that the PESRM has the potential to develop geotourism activities and that these could contribute to the knowledge, valorization and conservation of the existing geodiversity.